Efektivitas Penggunaan Busy Book Terhadap Kecerdasan Logika Matematika Anak Di Taman Kanak-Kanak - Ilham Sakri Alfaregi; Asdi Wirman (Universitas Negeri Padang, 2022)
This study aims to find out how effective the use of busy book on the logical intelligence of early childhood mathematics. This study linked 28 children as the object of research, including 14 children from the experimental class and 14 children from the control class. This type of research is quantitative with a quasi-experimental design, namely pre-test post-test control group. The data collection technique in this study used an assessment instrument by giving a score based on the achievement of child development in accordance with the indicators on the research instrument. Before carrying out the research, the instrument validity test was conducted, namely, joint testing with experts in the field of early childhood mathematics and testing of research instruments in order to obtain a valid and reliable instrument. The research data analysis technique uses the normality test to determine whether the research data is normally distributed and the homogeneity test to test whether the data is homogeneous. The next step is to measure whether there is a significant effect of using busy books on children's mathematical logical intelligence, then a hypothesis test and effect size test are carried out which obtain significant results of 0.003 which means significant or influential value, and the d value of effect size test is 1.23 which means it has an effect strong category